1955
DOI: 10.1084/jem.102.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells as Sources of Tissue Histamine

Abstract: Enumeration of mast cells and determination of histamine in sections of dog skin and dog lung have shown that the regions of the tissue rich in mast cells are also rich in histamine. In the skin, the outer layers of the dermis contain higher concentrations of histamine and mast cells than any other region. Average values of the histamine content and mast cell count for dog liver, heart, muscle, and kidney, and for beef liver parenchyma and capsule, also exhibit a positive relationship between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
1

Year Published

1956
1956
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(20 citation statements)
references
References 14 publications
2
17
0
1
Order By: Relevance
“…The value of histamine coincides with that reported by GRAHA~a et al (32.2 + 2.4 pg/mast cell, mean _+ S.D.) [11]. Whereas Riley reported values of 18 and 25 pg histamine/mast cell in calf and ox liver capsule [12].…”
Section: Content Of Aprotininsupporting
confidence: 91%
“…The value of histamine coincides with that reported by GRAHA~a et al (32.2 + 2.4 pg/mast cell, mean _+ S.D.) [11]. Whereas Riley reported values of 18 and 25 pg histamine/mast cell in calf and ox liver capsule [12].…”
Section: Content Of Aprotininsupporting
confidence: 91%
“…The mast cells are especially important in this respect. Specifically sensitized mast cells are degranulated by the allergic reaction, and histamine, bradykinin, and other transmitter substances are liberated (Graham et al, 1955;Katz and Cohen, 1941;Keller, 1966;Middleton, 1959). Slow-reacting substance A (SRS-A) is among the substances that are liberated in sensitized lung tissues by allergic reactions, but it is uncertain whether or not it origin- (1) spasm of smooth muscle, (2) oedema of mucosa, (3) increased secretion of viscidfluid, and (4) forced expiration to compensate for combination of factors 1, 2, and 3, causing increased external pressure on bronchi and bronchioles.…”
Section: Allergy and Bronchial Reactivitymentioning
confidence: 99%
“…Several workers have observed that mast cell population density varies considerably, not only between species and between difFerent tissues in the same species, but also from one region to another in the same tissue (Hellstrom & Holmgren, 1950;Riley & West, 1953, 1956Graham et al, 1955;Binazzi & Rampichini, 1959).…”
mentioning
confidence: 99%